Hospice Care Services Associated With a Lower Utilization of Life-Sustaining Treatments During End-Of-Life Care Among People Living With HIV/AIDS: A Population-Based Cohort Study. (October 2022) - Lai, Yun-Ju; Ko, Ming-Chung; Chan, Shang-Yih; Chou, Yi-Sheng; Wang, Chun-Chieh; Ku, Po-Wen; Chen, Li-Jung; Hsu, Li-Fei; Chuang, Pei-Hung; Chen, Chu-Chieh; Yen, Yung-Feng
Background: Hospice care involves improving quality of end-of-life (EOL) care and respecting patients' preferences regarding EOL treatment. However, the impact of hospice care services on the utilization of life-sustaining treatments during EOL care in patients with life-limiting diseases has not been extensively studied.Objectives: This nationwide cohort study aimed to determine the impact of hospice care services on the utilization of life-sustaining treatments during the last 3 months of life among people living with HIV/AIDS (PLWHA) in Taiwan.Methods: From 2000 to 2018, we identified adult PLWHA from Taiwan centers for disease control HIV Surveillance System. HIV-infected individuals were defined as positive HIV-1 Western blot. Life-sustaining treatments included cardiopulmonary resuscitation, intubation, mechanical ventilation support, and defibrillation. The association of hospice care services with the utilization of life-sustaining treatments was determined using multiple logistic regression.Results: Of 5691 PLWHA, 2595 (45.9%) subjects utilized life-sustaining treatments during the last 3 months of life. After adjusting for other covariates, PLWHA with hospice care services were less likely to receive life-sustaining treatments during the last 3 months of life than those without the services (adjusted odds ratio [AOR] = .50, 95% confidence interval [CI]: .37-.66). Considering the type of life-sustaining treatments, hospice care services were associated with lower likelihood of receiving cardiopulmonary resuscitation (AOR = .22, 95% CI: .13-.39), endotracheal intubation (AOR = .48, 95% CI: .35-.65), and mechanical ventilation support (AOR = .56, 95% CI: .42-.75).Conclusion: Hospice care services were associated with a lower utilization of life-sustaining treatments during the last 3 months of life among PLWHA.